2011
DOI: 10.1002/lt.22441
|View full text |Cite
|
Sign up to set email alerts
|

Sirolimus-based immunosuppression in liver transplantation for hepatocellular carcinoma: A meta-analysis

Abstract: Sirolimus (SRL) is a novel immunosuppressant with antitumor properties. We performed a meta-analysis to determine whether SRL can improve patient survival and decrease the risks of tumor recurrence in patients with a pretransplant diagnosis of hepatocellular carcinoma (HCC). We searched databases for controlled clinical trials assessing the survival and oncological benefits of SRL for liver transplant recipients with pretransplant HCC. Five studies with a total of 2950 participants were included in this study.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
113
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(117 citation statements)
references
References 28 publications
2
113
1
1
Order By: Relevance
“…26 Some initial studies showed higher incidence of hepatic artery thrombosis with use of Sirolimus, but it was not subsequently substantiated. 27,28 Conversion of CNI to Sirolimus is also useful for patients with CNI induced nephrotoxicity, [29][30][31] but it causes proteinuria and may worsen renal function in patients with pre-existing renal disease. 32,33 Sirolimus impairs wound healing as it impairs action of TGFb, 34 hence it is usually avoided in the early post operative period.…”
Section: Mtor Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…26 Some initial studies showed higher incidence of hepatic artery thrombosis with use of Sirolimus, but it was not subsequently substantiated. 27,28 Conversion of CNI to Sirolimus is also useful for patients with CNI induced nephrotoxicity, [29][30][31] but it causes proteinuria and may worsen renal function in patients with pre-existing renal disease. 32,33 Sirolimus impairs wound healing as it impairs action of TGFb, 34 hence it is usually avoided in the early post operative period.…”
Section: Mtor Inhibitorsmentioning
confidence: 99%
“…35 In a meta-analysis by Liang et al, including five studies (total 2950 patients), use of Sirolimus was associated with better 1, 3 and 5 year survival rates and odds ratio of 0.42 for hepatocellular carcinoma recurrence as compared to Sirolimus free regimens, without statistically significant increased incidence of hepatic artery thrombosis and acute cellular rejection. 28 …”
Section: Use Of Sirolimus As Anti-tumor Agentmentioning
confidence: 99%
“…A retrospective analysis of the SRTR database in the US suggested less recurrence in patients exposed to sirolimus. Two meta-analyses came to the same conclusion [20,21]. In addition, minimization of CNI exposure also seems to reduce recurrence.…”
Section: Exception 3: Hepatocellular Carcinomamentioning
confidence: 72%
“…Sirolimus inhibits T-cell proliferation by cell cycle inhibition and is sometimes used in OLT as a CNI-sparing strategy (for renal dysfunction) or in patients receiving a transplant for hepatocellular carcinoma or other malignancies (for antiproliferative effects). 73 Corticosteroids inhibit multiple cytokines, including interleukin 1, 2, and 6, tumor necrosis factor, and interferon ␥, and are most often used early after transplant and at times of acute cellular rejection. 15,74 The common adverse effects of these medications are listed in Table 4.…”
Section: Immunosuppressive Medicationsmentioning
confidence: 99%